Unique duplication of IFNh genes in Nile tilapia (Oreochromis niloticus) reveals lineage-specific evolution of IFNh in perciform fishes. Issue 107 (December 2020) - Gan, Zhen; Cheng, Jun; Xia, Liqun; Kwok, Kevin WH.; Lu, Yishan; Nie, Pin
Abstract: Fish appear to harbour a complex type I IFN repertoire containing subgroups a, b, c, d, e, f, and h, and IFNh is only reported in perciform fishes. However, no multiple copies of IFNh gene has been identified in fish to date. In this study, two IFNh genes named On-IFNh1 and On-IFNh2 were cloned from Nile tilapia, Oreochromis niloticus . The predicted proteins of On-IFNh1 and On-IFNh2 contain several structural features known in type I IFNs, and estimation of divergence time revealed that these two genes may have arisen from a much recent local duplication event. On-IFNh genes were constitutively expressed in all tissues examined, with the highest expression level observed in gill, and were rapidly induced in all organs/tissues tested following the stimulation of poly(I:C). In addition, both recombinant On-IFNh1 and On-IFNh2 trigger a relative delayed but sustained induction of interferon-stimulated genes (ISGs), whereas recombinant On-IFNc elicits a rapid and transient expression of ISGs in vivo . The present study thus contributes to a better understanding of the functional properties of tilapia interferons, and also provides a new insight into the evolution of IFNh in fish. Highlights: Multiple copies of IFNh gene were first discovered in fish. Tilapia IFNh genes may have arisen from a recent duplication event. Tilapia IFNh genes are significantly up-regulated following the stimulation of poly(I:C). Tilapia IFNc elicits a rapid and transient induction of ISG expression in vivo. Tilapia IFNh1 and IFNh2 trigger a relative delayed but sustained induction of ISG expression in vivo.